Elevated pulmonary arterial pressure and altered expression of Ddah1 and Arg1 in mice lacking cavin‐1/PTRF. Issue 1 (7th June 2013) - Swärd, Karl; Sadegh, Mardjaneh K.; Mori, Michiko; Erjefält, Jonas S.; Rippe, Catarina
Abstract: Caveolae are invaginations in the plasma membrane that depend on caveolins and cavins for maturation. Here, we investigated the pulmonary phenotype in mice lacking cavin‐1. Bright field and electron‐microscopy showed that the cavin‐1‐deficient mice lacked caveolae in the lung, had an increased lung tissue density, and exhibited hypertrophic remodeling of pulmonary arteries. The right ventricle of the heart moreover had an increased mass and the right ventricular pressure was elevated. A microarray analysis revealed upregulation of Arg1 and downregulation of Ddah1, molecules whose altered expression has previously been associated with pulmonary arterial hypertension. Taken together, this work demonstrates vascular remodeling and increased pulmonary blood pressure in cavin‐1 deficient mice and associates this phenotype with altered expression of Arg1 and Ddah1. Abstract : e00008 Abstract : Mutations in caveolin‐1 give rise to a heritable form of pulmonary arterial hypertension (PAH). Novel caveolae proteins have been identified in recent years. Here, we demonstrate that mice lacking cavin‐1 develop PAH accompanied by reciprocal changes in Ddah1 and Arg1 .